DIGITALISASI LOG BOOK PENGGUNAAAN ALAT LABORATORIUM PREKLINIK DI JURUSAN KESEHATAN GIGI POLTEKKES KEMENKES BANJARMASIN MENGGUNAKAN QR CODE - Nisa, Hilwatun; Pratama, Muhammad Yusril (Poltekkes Kemenkes Banjarmasin, 2025)
Laboratories play an important role in supporting the quality of learning, but administrative management often faces obstacles, especially in manual recording of equipment usage log books, which is ineffective and prone to omissions. Digitalization through the use of QR Codes is one innovation to improve efficiency, accuracy, and ease of data access. This study aims to determine the difference in student satisfaction levels before and after the implementation of a QR Code-based digital logbook in the Preclinical Laboratory of the Dental Health Department at Poltekkes Kemenkes Banjarmasin. The research design used was a Quasi-Experimental study with a one-group pretest-posttest design, involving 30 respondents selected through purposive sampling. The research instrument consisted of a student satisfaction questionnaire, with data analysis conducted using the Wilcoxon Signed-Rank Test due to the non-normal distribution of data. The results showed that the average student satisfaction increased from 3.36 before the intervention to 3.80 after the intervention, with a difference of 0.44. The Wilcoxon test yielded a p-value of 0.000 (<0.05), indicating a significant difference in student satisfaction before and after the use of the QR Code-based QR Code-based digital log book. It can be concluded that the implementation of a digital log book through QR Code can increase student satisfaction in laboratory services because it provides ease of recording, speed of access, data transparency, and administrative efficiency compared to manual methods.